Drug resistance and genetic transmission characteristics of HIV-1 CRF55_01B in people living with HIV/AIDS (PLWHA) in Henan Province, China - Jie Ma; Jinjin Liu; Shuguang Wei; Mingjie Hou; Qingxia Zhao; Yuqi Huo (Retrovirology)
Abstract Background Among the many CRFs, CRF55_01B was the first CRF01_AE and subtype B recombinant strain identified around 2013 among men who have sex with men (MSM) in Shenzhen, China. With rapid spreading throughout the country, CRF55_01B has attracted much attention in recent years. This study aimed to analyze its prevalence of drug resistance and transmission characteristics in people living with HIV/AIDS (PLWHA) in Henan province, China so as to pay particular attention to this group of individuals to reduce the incidence of drug resistance. Results Two hundred and forty-five CRF55_01B-infected individuals, including 141 treatment-naïve and 104 treatment-experienced individuals, were enrolled. In treatment-naïve individuals, 6.38% (9/141) of them harboured NRTI DRMs and 19.15% (27/141) of them harboured NNRTI DRMs except V179E/D. In treatment-experienced individuals, 2.00% (2/100) harboured INSTI DRMs, 82.69% (86/104) of them harboured NRTI DRMs, and 88.46% (92/104) of them harboured NNRTI DRMs except V179E/D. The overall prevalence of ADR was 89.42% (93/104), while the prevalence of PDR was 19.86% (28/141). A total of 23 transmission clusters, accounting for 37.55% (92/245) of the total sequences, were identified. The clusters ranged in size from 2 to 19, and 15 (65.22%) had 3 or more sequences. Conclusions High prevalence of DRMs and drug resistance were observed in CRF55_01B in both treatment-naïve and treatment-experienced individuals, particular attention should be paid to this group of individuals to reduce the incidence of drug resistance.